Сравнительные возможности программных средств аналитического описания экспериментальных данных в задачах диагностики свойств дисперсных материалов - Петасюк, Г.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The paper presents a multivariant approach to the question of empirical mathematical models construction and analysis. Developing on such approach base algorithm provides for automatic computer–aided generation of approximation relationships, definition of operational characteristics of derived mathematical models and analysis of their adequacy. Software support is created, we give examples of empirical mathematical models obtained by this software.